2006
DOI: 10.1038/sj.bjc.6603167
|View full text |Cite
|
Sign up to set email alerts
|

Differential disruption of cell cycle pathways in small cell and non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer-related mortality in the world, with small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) comprising the two major cell types. Although these cell types can be distinguished readily at the histological level, knowledge of their underlying molecular differences is very limited. In this study, we compared 14 SCLC cell lines against 27 NSCLC cell lines using an integrated array comparative genomic hybridisation and gene expression profiling approach to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 54 publications
3
88
0
Order By: Relevance
“…As has been shown recently, there are molecular differences between small cell cancer, large cell cancer, squamous cell cancer, and adenocarcinomas of the lung (33,34). As an example, EGFR mutations are more common in adenocarcinomas than the other histologies of lung cancer (40% versus 3%; ref.…”
Section: Discussionmentioning
confidence: 96%
“…As has been shown recently, there are molecular differences between small cell cancer, large cell cancer, squamous cell cancer, and adenocarcinomas of the lung (33,34). As an example, EGFR mutations are more common in adenocarcinomas than the other histologies of lung cancer (40% versus 3%; ref.…”
Section: Discussionmentioning
confidence: 96%
“…Since early articles on the molecular mechanisms perturbed in lung cancers (Slebos and Rodenhuis 1989;Nau et al 1985) until the most recent articles on this topic (Panani and Roussos 2006;Coe et al 2006), there is a consensus that the cell cycle is highly deranged in lung cancers. Moreover, cell cycle genes have started to be considered both as potential prognostic factors and therapeutic targets (Vincenzi et al 2006).…”
Section: ‫6מ‬mentioning
confidence: 99%
“…In a landmark clinical and molecular study, it was shown that the transcriptome profile of normal bronchial epithelium is distinct from that of the lung parenchyma, that this profile differs again between SCLC and NSCLC, and that there is in each individual an association between cumulative tobacco exposure and gene transcription [52,53]. In addition, the expression of a number of presumed oncogenes and tumour suppressor genes in the airway epithelial cells of smokers did not return to normal for decades after smoking cessation [54], although many others (especially the antioxidant and drug-metabolising genes) did so within 2 years.…”
Section: Genetics and Carcinogenesis Riskmentioning
confidence: 99%